Anomalous Adsorption of PFAS at the Thin‐Water‐Film Air‐Water Interface in Water‐Unsaturated Porous Media - Wenqian Zhang; Bo Guo (Water Resources Research)
Abstract Per‐ and poly‐fluoroalkyl substances (PFAS) are interfacially‐active contaminants that adsorb at air‐water interfaces (AWIs). Water‐unsaturated soils have abundant AWIs, which generally consist of two types: one is associated with the pendular rings of water between soil grains (i.e., bulk AWI) and the other arises from the thin water films covering the soil grains. To date, the two types of AWIs have been treated the same when modeling PFAS retention in vadose zones. However, the presence of electrical double layers of soil grain surfaces and the subsequently modified chemical potential of PFAS at the AWI may significantly change the PFAS adsorption at the thin‐water‐film AWI relative to that at the bulk AWI. Given that thin water films contribute to over 90% of AWIs in the vadose zone under many field‐relevant wetting conditions, it is critical to quantify the potential anomalous adsorption of PFAS at the thin‐water‐film AWI. We develop a thermodynamic‐based mathematical model to quantify this anomalous adsorption. The model couples the chemical equilibrium of PFAS with the Poisson‐Boltzmann equation that governs the distribution of electrical potential in a thin water film. Our model analyses suggest that PFAS adsorption at thin‐water‐film AWI can deviate significantly (up to 82%) from that at bulk AWIs. The deviation increases for lower porewater ionic strength, thinner water film, and higher soil grain surface charge. These results highlight the importance of accounting for the anomalous adsorption of PFAS at the thin‐water‐film AWI when modeling PFAS fate and transport in the vadose zone.